A Comprehensive Review On Recent Advancements In Nanosponges: Innovations, Biomedical Applications, And Future Perspectives - S, Kanna; S, Jeganath; Ahmed A, Syed Asad (Journal of Neonatal Surgery, 2025)
Nanosponges represent advanced nanostructures which boost drug dissolution properties and enhance preservation as well as distribution efficiency while controlling drug release patterns. The most researched nanosponge type known as cyclodextrin-based nanosponges provides targeted drug delivery through inclusion and non-inclusion complex approaches. Drug encapsulation and release efficiency improved through recent developments in synthetic methods which include microwave-assisted, ultrasound-assisted and hyper-crosslinking techniques. Drugs bound to nanosponges through carbon nanotube, silver nanowire and titanium dioxide integration improve the uptake rates and therapeutic effectiveness. These materials have proven useful in medical treatments of cancer alongside gene inhibition technologies and serving as protein carriers and environmental pollution treatment systems. Widespread clinical application remains limited because of nanotoxicity problems and technical scalability issues together with regulatory barriers. New studies will combine diagnosis elements with therapeutic capabilities while studying improved polymer-to-crosslinker stoichiometry for future economical environmentally-friendly synthesis methods. This review presents an extensive analysis of new nanosponge developments and their biomedical applications together with projections for future advancement as an effective nanomaterial in drug delivery systems and nanomedical practice.